Citra tubuh, asupan makan, dan status gizi wanita usia subur pranikah - Yhona Paratmanitya; Hamam Hadi; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2012)
Background: Premarital reproductive age women are prospective mothers whose nutritional status should be monitored, because it can affect the outcome of pregnancy. Premarital period can be interpreted as pre conception period. As the wedding ceremony approaches, women’s concern of their body image is increasing. Negative body image can influence their dietary intake and nutritional status. Research on the effect of pre wedding body image on women’s dietary intake and nutritional status in non-western countries is still limited.Objective: The aim of this research was to describe the relationship between body image, dietary intake and nutritional status of premarital reproductive age women in Yogyakarta city. Method: This research was an observational research with cross-sectional design. The subjects were 157 premarital reproductive age women in Yogyakarta city who came to the office of religious affairs to register their marriage or followed the premarital advisory program. Body image was measured by Body Shape Questionnaire (BSQ-34); dietary intake was measured by Semi-Quantitative Food Frequency Questionnaire (SQFFQ); and nutritional status was classified based on Body Mass Index (BMI). Data were analyzed with Chi-Square test, t-test and multiple logistic regression.Result: Only 12,1% of participant reported dissatisfied of their body image. Dominant factor that affect their body image was environmental influence (OR=14,5). Bivariat analysis showed that there was a significant relationship between body image and nutritional status (p<0,05; OR=15,6), as well as dietary intake and nutritional status (p<0,05). However, body image and dietary intake was not significantly associated (p>0,05). Multiple logistic regression analysis showed that factors associated with nutritional status were body image, carbohydrate intake and environmental influence. Conclusion: Body image was associated with nutritional status. However, body image does not affect dietary intake. Energy, protein, fat and carbohydrate intake were significantly associated with nutritional status.